(untitled) (Revista de Ciências Agroveterinárias, 2019)
Weed infestation is among the problems of greater interference in agriculture, and therefore has awakened the use of management techniques, as the use of solarization and mulching on the ground, that can mitigate this problem. Thus, was objectified with this work to evaluate the management of solarization and soil mulching on weed infestation in cowpea. The experiment was carried in greenhouse under a completely randomized design with eight treatments, such as: soil solarization (with and without) and three dead cover crops (castor bean, crotalaria and spontaneous vegetation + with four replications. The research was conducted in pots with a capacity of 11 dm3, filled with eight kg of soil, and the sowing was carried out directly in the pots. At 80 days after sowing, the number and total dry mass of weeds in each experimental unit were determined. During this period, the growth and yield characteristics of cowpea were also evaluated. The number and total dry mass of weeds were higher in the uncovered soil, independent of solarization, and the dry mass was higher in the absence of solarization. This weed infestation reduced the length of the main branch, number of leaves, number and length of pods, production of dry mass and amount of water in the aerial part of the cowpea, while increasing the root dry mass. Solarization, when isolated, does not totally suppress the incidence of weeds, but reduces their development. On the other hand, soil cover, independent of type and solarization, reduces the incidence of weeds favoring growth, yield and dry matter production in the aerial part of the cowpea.